Improving Zinc Concentration and Bioavailability of Wheat Grain through Combined Foliar Applications of Zinc and Pesticides. (1st May 2019) - Wang, Shaoxia; Zhang, Xiaoyuan; Liu, Ke; Fei, Peiwen; Chen, Juan; Li, Xiushuang; Ning, Peng; Chen, Yanlong; Shi, Jianglan; Tian, Xiaohong
Abstract : Core Ideas: Foliar zinc (Zn) applied together with any pesticides caused similar increase in whole grain and grain milling fractions Zn concentrations as compared with foliar Zn application alone. Foliar Zn applied simultaneously with pesticides significantly increased estimated Zn bioavailability in whole grain and grain milling fractions; the increases were comparable to foliar Zn application alone. Higher Zn concentration and bioavailability in whole grain with Zn applied at milk stage with or without pesticides indicated efficient absorption of Zn by wheat plants compared with Zn applied at flowering stage. ABSTRACT: Foliar ZnSO4 application has been shown to be effective for increasing Zn concentration in wheat ( Triticum aestivum L.) grain but is time and energy consuming. For promoting adoption of this practice by growers, a field experiment was conducted in two seasons to evaluate the effects of foliar Zn combined with six commonly used pesticides (three insecticides and three fungicides) applied at flowering or milk stage on Zn concentration and bioavailability in wheat grain and its milling fractions. Grains were fractionated into flour and bran for analysis of Zn, phytic acid (PA), and other nutrients (protein, P, K, Fe, and Mn). The results showed that foliar application of Zn together with various pesticides, irrespective of pesticide type, was as effective as foliar Zn application alone in improving Zn concentrations in whole grain and in its milling fractions. Combined foliar application of Zn with pesticides did not increase PA concentration but significantly increased the estimated Zn bioavailability in flour by 79.2%, in bran by 95.4%, and in grain by 94.5%. Zinc foliar application (with or without pesticides) at milk stage resulted in a higher Zn concentration and bioavailability in whole grain than Zn applied at flowering stage. There were no adverse effects of combined foliar application of Zn and pesticides on grain yield and other nutrients. Therefore, foliar Zn application can be safely applied with commonly used fungicides or insecticides (particularly at milk stage) to enrich Zn of the whole grain and particularly the flour and represents a useful practice for overcoming human Zn deficiency.